2018
DOI: 10.1177/1351010x18772026
|View full text |Cite
|
Sign up to set email alerts
|

Review of acoustic comfort evaluation in dwellings: part II—impact sound data associated with subjective responses in laboratory tests

Abstract: The concept of acoustic comfort is hardly defined and used to refer to conditions of low noise levels or annoyance based on standardized descriptors. Airborne and impact sound measurements are used to rate acoustic comfort in dwellings, but they often do not express human perception of noise or comfort. If the descriptors are statistically associated with self-reported responses, they can be used as prediction models and considered sufficient for acoustic comfort assessment. This review article presents studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…The fulfillment of the criteria is rated in this review in a scale of high (+++), moderate (++), low (+), as happened in the previous parts. 1,2 The results are tabulated in Table 3 while the Bradford Hill's criteria are as follows:…”
Section: Evaluation Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fulfillment of the criteria is rated in this review in a scale of high (+++), moderate (++), low (+), as happened in the previous parts. 1,2 The results are tabulated in Table 3 while the Bradford Hill's criteria are as follows:…”
Section: Evaluation Of Included Studiesmentioning
confidence: 99%
“…It is accompanying part I, which reviewed subjective responses to field data from building surveys 1 and part II, which reviewed subjective responses to impact sound data in laboratory tests. 2 This article is focused on subjective responses relevant to airborne sound data used in laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic comfort seems to be rather determined by more factors than just the sound level [15,16]. For a review of the variety of definitions, descriptions, and indicators of acoustic comfort, see [20,21,22]. The study reported in this paper uses a subjective evaluation of acoustic comfort and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Building occupants are exposed to a variety of distinct environmental conditions, including thermal, visual, aural, and olfactory stimuli. An extensive body of literature (including review papers) deals with single-domain influences, such as thermal [34][35][36][37], visual [38,39], or aural [40,41] perception. In comparison, fewer research efforts have been conducted to explore multi-domain exposure situations.…”
Section: State Of the Artmentioning
confidence: 99%